Towards European Union or Regional Economic Area: Western Balkans at crossroads - Gazmend Qorraj (Naše gospodarstvo / Our Economy, 2018)
The aim of the paper is to reflect upon the dilemma or whether the EU will continue the integration process in the Western Balkans or backlash on regional cooperation instruments and initiatives within the framework of the Western Balkans. The Regional Economic Area (REA) is analyzed as the more recent policy of the European Union for the remaining Balkan countries. It is crucial to analyze the idea behind REA, starting from two main assumptions: first, the creation of REA stemmed from EU internal challenges; and second, REA came up as a creative EU approach in efforts to find a specific model for reforms in the Western Balkans in the frame of regional institutions. The paper also discusses regional trade and specifically the role of the Regional Cooperation Council (RCC) in coordinating these initiatives in the Western Balkans. Taking into consideration the EU current challenges as well as difficulties of the Western Balkan countries to overcome the political and economic problems, then regional cooperation could appear as an alternative to the EU integration process for the Western Balkans. The main conclusion of this paper is that the Western Balkans needs the EU's direct support, in particular, since RCC and other regional instruments cannot enforce, support and monitor the initiatives and reforms in the region.
Keywords: B22; F15; J61; 330; Western Balkans; integration; cooperation; coordination; regional; enlargement